PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID PADA MATA PELAJARAN BIOLOGI KELAS XI DI SMA - Hary Diraysidi; Abna Hidayati; Syafril Syafril (Universitas Negeri Padang, 2024)
This study aims to develop an Interactive Multimedia Application for Biology subjects using the iSpring Suite 9 application. This Interactive Multimedia is designed to enable students to learn independently and visually. The research employs the Research & Development method with validation tests conducted by three experts: two media experts and one subject matter expert. A trial was conducted with 15 eleventh-grade students from SMAN 3 Pariaman to test the practicality of the application. The media validation results showed an average score of 4.56 with a percentage of 89% (highly valid) for media validator 1, and an average score of 4.28 with a percentage of 83% (highly valid) for media validator 2. The subject matter validation achieved an average score of 4.72 with a percentage of 94% (highly valid). The practicality test results showed an average score of 4.37 with a percentage of 87.72% (highly practical). Based on these results, the developed Interactive Media is considered valid and practical for teaching Biology to eleventh-grade high school students.